The ideology of Assyria: The historiography of the problem - S.B. Krikh; A.A. Popova (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper considers the problem of Assyriology development in the context of the general evolution of research on history. Assyriology has undergone the following several stages in its development: 1) middle 19th century – 1920s: collection, translation, and initial interpretation of data obtained during the archaeological expeditions; 2) 1930s – 1950s: creation of generalizing works, attempts to characterize the specificity of the state structure and royal power of Assyria; 3) late 1960s – early 21st century: the modern stage in Assyriology development, attempts to apply new approaches to the study of the history of Assyria. Based on how modern Assyriologists consider the problem of the ideology of Assyria, we tried to show that the newest theoretical and methodological approaches, such as the ones developed by R.J. Thompson, L.R. Siddall, B. Pongratz-Leisten, and M. Karlsson, are applied currently in the field of Assyriology. During the review of these monographs, the following conclusion has been made: the development of the methodological foundations of history research and their introduction into various spheres of historical knowledge, on the one hand, expanded the problematic field of Assyriology and allowed us to look at the archaeological sources from different perspective based on new data which were not earlier available to researchers. However, on the other hand, using the example of ideology, we have shown that researchers, due to differences in the applied approaches, see the problem of studying ideology and understand the basic terms in different ways. It leads to different results of research that cannot be combined within the framework of a single cognitive space.